Gas permeation performance of polysulfone-zeolite 4a hollow finer mixed matrix membrane using 3-aminopropyltriethoxysilane as silane agent - Wahab, M. F. A.; Ismail, A. F.; Shilton, S. J. (Faculty of Chemical Engineering & Natural Resources, 2008)
This study is performed primarily to investigate the effect of chemical modification on zeolite surface towards gas separation performance of hollow fibers mixed matrix membrane. In this study, polyethersulfone (PES)–zeolite 4A mixed matrix hollow fiber membrane for modified and unmodified zeolite was spun using dry/wet spinning technique. The modified zeolite 4A was prepared by treating the zeolite with Dynasylan Ameo (DA) silane agent to allow PES chains to be grafted on zeolite surface. The results from the Field Emission Scanning Electron Microscopy (FESEM), DSC and Fourier transform infrared spectroscopy (FTIR) analysis confirmed that chemical modification on zeolite surface had taken place. ‘Sieve-in-a-cage’ morphology observed the poor adhesion between polymer and unmodified zeolite. FESEM's cross-section view indicated good compatibility between polymer and zeolite for PES–modified zeolite. The gas separation performance of the mixed matrix hollow fiber membranes with modified zeolite were relatively higher compared to that of the hollow fiber mixed matrix membranes with unmodified zeolite. PES–modified zeolite 20 wt% silane yielded significant selectivity enhancement of 7.26 and 46.28 for O2/N2 and CO2/CH4, respectively.